Coupled numerical approach combining X-FEM and the embedded discrete fracture method for the fluid-driven fracture propagation process in porous media. (June 2020) - Wang, Cong; Huang, Zhaoqin; Wu, Yu-Shu
Abstract: A coupled simulation strategy combining the embedded discrete fracture method (EDFM) and the extended finite element method (X-FEM) is developed to simulate the fluid driven fracture propagation process in porous media. This physical process includes three strong coupling mechanics: fluid flow in fractures and porous media, solid deformation with fractures, and fracture propagations. The EDFM and X-FEM are used to simulate fracture-related fluid mechanics and solid mechanics, respectively, with information exchanged under the iterative numerical coupling scheme. Mathematical equations on how to link these independent modules as well as numerical techniques on how to accelerate the coupling convergence rate are discussed in detail. Both X-FEM and EDFM avoid the cumbersome construction of unstructured grids to capture fracture paths and also avoid the remeshing for the fracture growth. They are first validated via benchmark problems individually and then are coupled to simulate fracture propagation problems in two dimensions and in three dimensions. Simulated multiphysics fields meet understandings qualitatively, and simulated fracture parameters (length, width and net pressure) match with analytical solutions quantitatively.